VARIABILITY OF THE ICE CONDITIONS IN THE CHUKCHI SEA AND THEIR LINKS WITH ARCTIC OSCILLATION - V. V. Plotnikov; N. M. Vakulskaya; L. I. Mezentseva; V. A. Dubina; V. I. Pustoshnova (Известия ТИНРО, 2020)
Variability of the ice conditions in the Chukchi Sea is considered in various scales on the basis of all available information for 1950–2017. Its dependence on the atmospheric circulation patterns measured with the Arctic Oscillation index is shown. Tendency to the ice reducing has intensified in the early 21st century in the Chukchi Sea that is accompanied with changes in its seasonal development, as shift of the ice destruction beginning from June to July, gradual increasing of the ice destruction rate till September, shift of the ice formation beginning from September to October, and delay of the ice spreading over entire sea area from November to December. Relationship of the ice conditions in the Chukchi Sea on summer phase of Arctic oscillation is detected: the maximum positive values of the index always correspond with heavy ice conditions, the minimum values of the index correspond with low-ice conditions only, and various ice conditions are observed in other years without neither positive nor negative extremities of Arctic oscillation. However, winter phase of Arctic oscillation does not affect on the ice conditions in the Chukchi Sea in June-November.